2011
DOI: 10.17221/133/2011-pse
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhiza enhances nutrient uptake in chickpea

Abstract: Arbuscular mycorrhiza fungi (AMF) colonize roots of host plants and promote plant growth due to improved uptake of nutrients. While the effects on P uptake are well known, the relevance of AMF for the uptake of other nutrients is less investigated. In the present paper we studied contents of N, P, K, Ca, Mg, Fe, Mn, Cu, and Zn in the legume chickpea in pot experiments during two seasons. Beside the control, the following treatment combinations: (i) the inoculation with the commercial AMF product 'Symbivit ® ';… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 28 publications
4
45
2
4
Order By: Relevance
“…The authors suggested that both bipartite and tripartite symbioses contributed to better plant nutrition, particularly regarding N and P, which resulted in improved plant growth. Enhanced nutrient uptake in inoculated chickpea has also been demonstrated by Farzaneh and colleagues …”
Section: Resultssupporting
confidence: 55%
“…The authors suggested that both bipartite and tripartite symbioses contributed to better plant nutrition, particularly regarding N and P, which resulted in improved plant growth. Enhanced nutrient uptake in inoculated chickpea has also been demonstrated by Farzaneh and colleagues …”
Section: Resultssupporting
confidence: 55%
“…It has been shown that mycorrhizal plants may have fewer and shorter roots than non-mycorrhizal plants, since extraradicular AMF mycelium increases the volume of soil explored by the plant root system, allowing higher water and nutrient uptake (Locatelli et al, 2002). Therefore, these results confirm the ability of AMF to benefit plant growth, and the increase in shoot and root biomass is consistent with previous studies with grapevine rootstocks (Dalla Costa et al, 2010;Anzanello et al, 2011;Cangahuala-Inocente et al, 2011) or with other plant species (Lovato et al, 2006;Farzaneh et al, 2011;Cavagnaro et al, 2012;Evelin et al, 2012;Mohandas, 2012;Steinkellner et al, 2012). Anzanello et al (2011) detected an increase in shoot and root biomass in SO4 and P1103 rootstocks inoculated with AMF, and Dalla Costa et al (2010) also showed an increase in shoot biomass in SO4 rootstock inoculated with AMF.…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, Heggo, Angle, and Chaney () showed a reduction of Zn uptake in mycorrhized plants cultivated in contaminated soils, and the AM was responsible for a larger root uptake of Cd, Co, Pb, and Zn in plants grown in control soils. Farzaneh, Vierheilig, Lössl, and Kaul (), Bi, Li, Christie, Hu, and Wong (), and Nogueira, Nehls, Hampp, Poralla, and Cardoso () also showed an increase in Zn and Cu uptake by mycorrhized plants grown in not contaminated soils. This different behaviour of mycorrhiza regarding the uptake of metals can be attributed to their different concentration in the soil.…”
Section: Resultsmentioning
confidence: 92%